Influence of the pattern of hypertrophy on left ventricular twist in hypertrophic cardiomyopathy - van Dalen, B M; Kauer, F; Soliman, O I I; Vletter, W B; Michels, M; Cate, F J ten; Geleijnse, M L (Heart (British Cardiac Society), 2009)
Background/objective: Left ventricular (LV) twist has an important role in LV function. The influence of the pattern of LV hypertrophy on LV twist in hypertrophic cardiomyopathy (HCM) patients is unknown. This study sought to assess LV twist in a large group of HCM patients according to the pattern of LV hypertrophy. Methods: The final study population consisted of 43 patients with HCM (mean age 43 (15) years, 31 men) and a typical sigmoidal (n = 16) or reverse septal curvature (n = 27) and 43 age-matched and gender-matched healthy control subjects. LV peak systolic rotation (Rotmax), LV peak systolic twist (Twistmax) and untwisting at 5%, 10% and 15% of diastole were determined by speckle tracking echocardiography (STE). Results: Compared to control subjects, HCM patients had increased basal Rotmax (−5.5° (2.3°) vs −3.4° (1.7°), p<0.001) and comparable apical Rotmax (7.3° (3.1°) vs 7.0° (2.2°), p = NS), resulting in increased Twistmax (12.4° (4.0°) vs 9.9° (2.7°), p<0.01). Untwisting at 5%, 10% and 15% of diastole was decreased in HCM patients (all p<0.05). There was a striking difference in apical Rotmax (9.4° (2.8°) vs 6.0° (2.6°), p<0.01) and Twistmax (15.3° (3.2°) vs 10.6° (3.3°), p<0.01) between HCM patients with a sigmoidal and reverse septal curvature. Conclusions: STE may provide novel non-invasive indices to assess LV function in patients with HCM. Apical Rotmax and Twistmax in HCM patients are dependent on the pattern of LV hypertrophy.